Pengaruh Return On Asset, Net Profit Margin, Debt to Equity Ratio Terhadap Modal Disetor Pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2013-2017 - Meme Rukmini (POLITEKNIK CAHAYA SURYA, 2020)
This study aims to analyze the Effect of Return On Assets, Net Profit Margins, Debt to Equity Ratio Against Paid Up Capital in Manufacturing Companies on the Indonesia Stock Exchange in 2013-2017. Significant test results show that, return on asset margin has a positive effect on paid profits. Variable Net Profit Margin, debt to equity ratio has no significant effect on paid up capital. Based on the results of the significant test, it has been proven that the variable return on assets. Net profit margin and debt to equity ratio have a positive effect on paid up capital.Keywords : Return on Asset , Net Profit Margin and Debt to Equity Ratio, Capital